The Influence of the Teachers Personality Competency on the Students Moral Attitude in Vocational School - Siagian, Liber; Halking; Habeahan, Sampitmo; Sitorus, Novandiwan (Jurnal Pendidikan Indonesia, 2022)
The competence of a teacher is a combination of personal, scientific, technological, social, and religious competencies which in general are the competencies of a teacher which includes material management, student understanding, pedagogic learning, personal development, and professional development. Teacher competence is a factor that can affect the quality of learning output. This study aims to analyze the effect of teacher personality competence on the moral attitudes of grade XI students. This type of research uses correlational research using quantitative descriptive research methods so that data analysis is carried out using statistical techniques to test hypotheses. Data collection using questionnaires, observation and documentation. The results of this study indicate that the moral attitude of grade XI students has an impact of 15.21% on the teacher's personality competence. This is evidenced by rcount more than rtable or 0.39 more than 0.304 so that the correlation coefficient of the X and Y variables is significant, where rtable n = 42 with an error rate of 50.304. The results of the t test study gave a t value of 2.441 and a t table of 2.021 at a significance level of 5 degrees of freedom (dk) = n-2 (42 -2 = 40), namely .H. t-count is more than t-table (2,441 more than 2,021). This shows that the alternative hypothesis can be accepted, namely the teacher's personality competence influences the moral attitude of grade XI students.